Fabrication of Silk Nanofibres with Needle and Roller Electrospinning Methods. (8th September 2014) - Sasithorn, Nongnut; Martinová, Lenka
Abstract : In this study, silk nanofibres were prepared by electrospinning from silk fibroin in a mixture of formic acid and calcium chloride. A needle and a rotating cylinder were used as fibre generators in the spinning process. The influences of the spinning electrode and spinning parameters (silk concentration and applied voltage) on the spinning process, morphology of the obtained fibres, and the production rate of the spinning process were examined. The concentration of the spinning solution influenced the diameter of the silk electrospun fibres, with an increase in the concentration increasing the diameters of the fibres in both spinning systems. The diameters of the electrospun fibres produced by roller electrospinning were greater than those produced by needle electrospinning. Moreover, increasing the concentration of the silk solution and the applied voltage in the spinning process improved the production rate in roller electrospinning but had less influence on the production rate in needle electrospinning.